OS06.6.A Real-World Pattern of Care Study on Glioblastoma in the Austrian Population. Final results from 2014-2020. (5th September 2022) - Oberndorfer, S; Woehrer, A; Borkovec, M; Marosi, C; Payer, F; Urbanic-Purkart, T; Nowosielski, M; Iglseder, S; Stockhammer, G; Kleindienst, W; Florea, C; Hager, A; et al.
Abstract: Background: The Austrian ABTR-SANO Glioblastoma Registry is the first population-based assessment of patterns of care for patients with Glioblastoma across Austrian healthcare institutions. The primary aim is to assess the real world effectiveness of administered therapies. Material and Methods: Clinical data are collected via a common web-based IT platform "ABTR-SANO Net" since 2014. The database and the ongoing evaluation of clinical parameters, as well as interims analysis are provided in cooperation with a review board. First Outcome analysis, including patients from 2014-2020, was performed at the end of 2021. Results: Eleven centers across Austria are involved, and the data of 1416 patients (m/f ratio: 1, 35, median age: 66 years) were recently analyzed in detail. Age, extent of resection, as well as ECOG was associated with improved survival. Methylated MGMT Status also showed a moderate survival benefit. Patients with re-resection and re-radiation also exhibited improved survival, which however may be attributed to a selection bias.Second line treatment manly comprised of antiangiogenic treatment, followed by alkylated agents, re-radiation and re-surgery. Median overall survival of all patients was 344 days and clearly age dependent (best for <50 years, worse for>80 years). Conclusion: This is the first population based outcome analysis of Glioblastoma in Austria. Results regarding prognostic markers and outcome are mostly comparable with international data. Robust population based data are important in order to monitor quality of health care, and to match the data with results from clinical studies.